Trends on the Artificial Fertilizer Market and in Fertilizers Use in Hungary - Ács, Gergő (Applied Studies in Agribusiness and Commerce, 2018)
The fertilizer market in Hungary is rather concentrated, which has a strong influence on the price of the fertilizer. Our domestic fertilizer use is primarily determined by that of nitrogen. The use of phosphorus is also significant but the trends in the use of potassium do not match the total quantities applied in individual years. Consequently, it can be concluded that the majority of farmers still focus on the application of nitrogen and also apply phosphorus but either neglect or do not pay enough attention to potassium fertilization. The changes in fertilizer prices between 2006 and 2017 can be broken down into two periods. Until 2012 a very important and dynamic increase was observed as a result of which the prices of N, P and K fertilizers increased by 80-120%, 160% and about 120%, respectively. This was followed by a downturn in the market and in relation to 2012 prices there were 20-30/ decreases experienced until 2017 but the rate of this lagged behind the prices in other European countries. Owing to this trend the prices of N, P and K have increased by 60%, 100% and 80%, respectively, over the past ten years. The correlation between fertilizer application and the prices of fertilizers in any given year is low but there is a positive one observed between fertilizer application and the fertilizer prices in the preceding year. This means supposedly that farmers mostly buy the fertilizers they wish to apply not in the current but in the preceding year and store them until these are applied. There is a strong correlation seen between fertilizer prices and the prices of corn and wheat, which means that fertilizer traders also keep tabs on economic results and also increase fertilizer prices under the influence of higher prices. Furthermore, it can be claimed that there is no correlation between crude oil prices on the world market and domestic N fertilizer prices. This is an important factor since the primary base material of N fertilizers is natural gas and their production involves considerable energy costs as well. It can be seen, however, that this is not what determines our domestic fertilizer prices, which can be explained by the fact that the price calculations by the determining actors on the Hungarian fertilizer market is not based on costs but on the demand. JEL Classification: Q13